Remote sensing handbook for tropical coastal management - Green, E.P.; Green, Edmund P. (Edmund Peter) 1965-.; Edwards, Alasdair J.; Mumby, Peter J.; Clark, Christopher D. (Paris Unesco Pub., 2000)
Coastal management sourcebooks; 3
Keywords: Coastal zone management -- Tropics -- Remote sensing -- Handbooks, manuals, etc; Tropics -- Remote sensing -- Handbooks, manuals, etc; Marine resources -- Tropics -- Remote sensing -- Handbooks, manuals, etc